NATIONAL HIGHER EDUCATION TRANSFORMATION DURING THE COVID-19 PANDEMIC IN PERCEPTIONS OF STUDENTS AND TEACHERS - Mospan, Natalia (Educological discourse, 2021)
This article examines the response of national higher education to the COVID-19 pandemic in 2020. In the hard year of 2020, students and teachers faced a new challenge – the transition to digitally-based distance education. They were forced to master previously unknown educational platforms, change the format and methods of teaching, learning and exams. Therefore, students and teachers’ attitudes and experiences of teaching-learning in such an emergency is a source for decision-making to improve the digital transformation of national higher education. The research focuses on the study of experience and perception by teachers and students of distance learning. The study is based on a survey of students of the capital university and teachers of three national universities, which give a clear idea of ​​the rapid transition of higher education to a new format – to digitally-based distance learning in an emergency – pandemic COVID-19. The questionnaires were developed in Google Forms format and distributed selectively to students and academics online in 2020-2021. It is emphasised that the COVID-19 pandemic tested the autonomy of national universities, their ability to reorganise educational services into an online format in a short time based on various technical capabilities and financial resources. The findings suggest that the COVID-19 pandemic has accelerated the digitisation of higher education, both international and national. In addition, the survey results allow not only to identify positive and negative trends in the digital transformation of higher education but also to outline promising formats of education in perceptions of students and teachers in the future.